Trichofolliculoma on gluteal area: A unique case report - Sinan Can Taşan; Canten Tataroğlu; Ekin Şavk; Fatma Nalbant (Galenos Publishing House, 2022)
Trichofolliculoma is a rare benign cystic nodule, consisting of a central dilated hair follicle that radiates into the surrounding dermis. Trichofolliculoma presents as a dome-shaped, solitary, 0.5-1.0 cm diameter of papule or nodule with a central pore. The clinical differential diagnosis of trichofolliculoma includes basal cell carcinoma, milia, keratoacanthoma, trichoepithelioma, and syringoma. Histopathological differential diagnosis includes trichoepithelioma, dilated pore of Winer, pilar sheath acanthoma, and basal cell carcinoma. Trichofollicumas usually occur on the face and less frequently on the neck and scalp. The gluteal area is an unprecedented site for trichofolliculoma although some unusual locations were observed. Herein, we report a very rare trichofolliculoma of the gluteal area which was not reported in English literature.